Exploring the perceptions of male student activists in relation to gender transformation and equality: the case of Wits - Nyaose, Thandazile (My University, 2017)
This research report explores how male Wits university students, who are actively involved in SASCO, a student organisation that advocates for amongst other things, none sexist society, perceive gender transformation and equality. The research approach utilised was qualitative and exploratory in nature with a broad aim of explaining the perceptions of the male students. Informal interaction and semi-structured individual interviews were conducted with ten male student activists and a key informant as methods of data collection. The data, in the form of interview transcripts was than analysed using the IPA approach. Although the participant’s perceptions of gender transformation and equality varied, it was evident, however, that all of the participants agreed that women have been previously and currently disadvantaged in society. The main findings that show the concepts of gender transformation and equality are much more digestible on paper and policies but difficult to implement. It becomes unreasonable to aspect individuals when they get into institutions of higher learning to now unlearn patriarchy and disown patriarchal privileges and benefits that they have enjoyed for most of the lives. The introduction of sustainable gender transformation and equality needs a complete overhaul of gendered societies and societal injustices. Gender injustices should be afforded the same attention that is given to economic inequalities, access to education and political instabilities.
A report on a research study presented to the Department of Social Work School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirement for a degree Master of Arts in Social Work, March 2017
Keywords: Equality--South Africa; Masculinity--South Africa; Feminism--South Africa; Sex discrimination against women--South Africa